Pemodelan Matematika Tipe S1S2E1E2I1I2T Pada Diabetes Melitus Tipe 2 Dengan Mempertimbangkan Treatment Yang Diakibatkan Adanya Pengaruh Obesitas - Saragih, Sisca Sri Dewi; Tarigan, Lola Zeramenda Br; Ahkrizal, Afdhal; Hasibuan, Hokkop Efendi (Universitas PGRI Semarang, 2025)
Diabetes Mellitus Type 2 is one of the largest contributors to the world of health in non-communicable diseases in Indonesia. Many people are affected either because of genetic obesity or obesity due to food. Mathematical modeling is one way to visualize the development and spread of Type 2 diabetes mellitus. The model used in this study is S1S2E1E2I1I2T and its stability will be seen. The article discusses the stability of fixed points using the Jacobian matrix and the Routh-Hurwitz criteria as well as the Castilo-Chaves and Song Theorem, reproduction numbers, and their numerical analysis.